A Model for Understanding and Changing the Practice of Leadership in Ukraine - Michael Linville; Artem Kliuchnikov (Business Ethics and Leadership)
The practice of leadership dates to humankind’s earliest history. However, the study of leadership is a much more recent phenomenon. Leadership is understood and practiced differently from culture to culture, though much academic research has been rooted in Western thought. Leadership exists in every facet of our lives because the societies around us significantly shape our very existence. Groups of people exist because, for most tasks and functions, groups can outcompete individuals. The very nature of groups is that they function best with one or more who serve as leaders while others serve as followers. As a result, the study of leadership facilitates a better understanding of the interpersonal dynamics between leaders and followers. In its simplest form, leadership may be understood as one individual influencing another, especially to work together to accomplish some common goal. The Analytical Center for Leadership Research and Development (ACLRD) has devoted the past several years to studying leadership theory and practice in Ukraine. This white paper summarizes that research, its purpose, methodology, and findings in providing the reader with analysis and insights into how leadership in Ukraine is perceived and practiced. In addition, this white paper proposes specific recommendations and the implementation of a research-based ACLRD Leader Model distinctly unique to Ukrainian culture and practices. Ultimately, this paper serves as a call for changes in the practice of leadership that hold great potential for benefiting Ukrainian organizations of all kinds as well as society at large.